2016
DOI: 10.1177/0886260516672937
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Shame in the Relation Between Peer Victimization and Mental Health Outcomes

Abstract: Youth who experience peer victimization are at risk of developing mental health problems. However, little is known about the emotional causal mechanisms linking peer victimization with these negative outcomes. This study investigated whether shame mediated this relationship. At three time points (T1-T3), 396 10- to 13-year-olds completed measures of peer victimization, shame (characterological, bodily, and behavioral; shame proneness), and mental health (depression, social anxiety, and externalizing behavior).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 79 publications
6
20
0
Order By: Relevance
“…At all levels of witnessing, victimization was associated with greater shame, which was associated with greater depressive symptoms. This finding extends past research that identifies shame as a mediator of the relationship between bullying victimization and depressive symptoms among adolescents (Duarte et al, 2015; Irwin et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At all levels of witnessing, victimization was associated with greater shame, which was associated with greater depressive symptoms. This finding extends past research that identifies shame as a mediator of the relationship between bullying victimization and depressive symptoms among adolescents (Duarte et al, 2015; Irwin et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…For example, adolescents who are more shame prone and depressed may be less likely to witness others' harassment, due to their being more isolated and/or self-focused. Furthermore, recent findings suggest that there may be bidirectional associations among bullying victimization, shame, and depressive symptoms (Irwin et al, 2019) and between sexual harassment victimization and depressive symptoms (Dahlqvist, Landstedt, Young, & Gådin, 2016). Future longitudinal research that measures changes in young people's environments and changes in experiences of shame and wellbeing will help better understand this phenomenon and the role that witnessing sexual harassment has on these associations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as research on violence and shame has shown, this may lead to increased psychological distress over time. The scarce literature investigating this relationship supports that shame following bullying may lead to impaired mental health in adolescents, as it negatively affects cognitions, moods, and behaviours (Irwin et al, 2016). Considering the high correlation between psychological distress and impaired functioning, feelings of shame may affect this aspect as well.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the bullying literature has mainly focused on the shame experienced by the bully or bystander, not shame experienced by the target of bullying (Ahmed & Braithwaite, 2004; Mazzone, Camodeca, & Salmivalli, 2016; Olthof, 2012; Olthof, Schouten, Kuiper, Stegge, & Jennekens-Schinkel, 2000). A recent study found that the victim’s shame mediated the association between experiencing peer victimization and a range of psychological distress in adolescents, suggesting that shame may be a mechanism by which peer victimization may influence mental health (Irwin, Li, Craig, & Hollenstein, 2016). …”
Section: Introductionmentioning
confidence: 99%